2019
DOI: 10.2174/1874331501913010156
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Mycelial Growth of Rhizoctonia Solani by Chitosan in vitro and in vivo

Abstract: Objective: Evaluate the antifungal effect of chitosan against Rhizoctonia solani in vitro and the possible mechanisms of its induced activity in potato tubers to control black scurf disease. Methods: The in vitro influence of chitosan at different concentrations on mycelial growth of R. solani was tested by using the poisoned food technique in PDA medium. The effect of these concentrations on the development of lesion diameters in tubers inoculated with R. solani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…In addition, the higher the concentration used, the higher the antifungal activity observed in our tests. The concentration-dependent phenomenon was also reported in previous research [17,33,34], which may be due to the strong interactions between chitosan's positive charges and the cell's negatively charged membranes [35]. As can be seen from the figures, SCNs wholly suppressed the mycelium linear growth, and biomass tested at a concentration of 200 ppm.…”
Section: Pathogenicity Testsupporting
confidence: 82%
See 1 more Smart Citation
“…In addition, the higher the concentration used, the higher the antifungal activity observed in our tests. The concentration-dependent phenomenon was also reported in previous research [17,33,34], which may be due to the strong interactions between chitosan's positive charges and the cell's negatively charged membranes [35]. As can be seen from the figures, SCNs wholly suppressed the mycelium linear growth, and biomass tested at a concentration of 200 ppm.…”
Section: Pathogenicity Testsupporting
confidence: 82%
“…Chitosan has been reported to have high fungal activity against many phytopathogenic fungi [10,11], which cause several fungal plant diseases [12][13][14]. Recently, chitosan-based nanoparticles have been widely studied for various applications because of their small size, good biocompatibility and degradability, high permeability, high antimicrobial property, low cost, and facile preparation [15][16][17][18][19]. Practically, chitosan nanoparticles have affected and prevented the growth of fungi on citrus fruits, such as P. steckii and A. oryzae [17], C. albicans [20,21], A. fumigatus [22], and Xanthomonas oryzae pv.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan at 4.0 g/l applied as soil drench showed significant levels of protection against soil-borne fungi, for example, Fusarium wilt on potato plants [38] and tomato [39]. Chitosan can induce defense activity in potato tubers against Fusarium dry rot [40] and Rhizoctonia solani [12]. Pre-harvest application with CaCl 2 and Chitosan was effective in minimizing weight loss and decay, as well as in maintaining maximum firmness and lengthening the shelf life of "Early Swelling" peach [41].…”
Section: Dry Rot Disease Incidencementioning
confidence: 99%
“…Chitosan (β-1,4-D-glucosamine), is a natural biopolymer obtained by deacetylation of chitin, the second most plentiful natural polymer in the world [10]. Chitosan is a resistance activator and an antifungal agent [11,12]. Many studies showed that chitosan could increase productivity, reduce transpiration, and induce more resistance to fungal, bacterial, and viral infections [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation